Changes in sediment methanogenic archaea community structure and methane production potential following conversion of coastal marsh to aquaculture ponds. (15th July 2022) - Yang, Ping; Tang, Kam W.; Tong, Chuan; Lai, Derrick Y.F.; Wu, Lianzuan; Yang, Hong; Zhang, Linhai; Tang, Chen; Hong, Yan; Zhao, Guanghui
Abstract: Widespread conversion of coastal wetlands into aquaculture ponds in coastal region often results in degradation of the wetland ecosystems, but its effects on sediment's potential to produce greenhouse gases remain unclear. Using field sampling, incubation experiments and molecular analysis, we studied the sediment CH4 production potential and the relevant microbial communities in a brackish marsh and the nearby aquaculture ponds in the Min River Estuary in southeastern China. Sediment CH4 production potential was higher in the summer and autumn months than in spring and winter months, and it was significantly correlated with sediment carbon content among all environmental variables. The mean sediment CH4 production potential in the aquaculture ponds (20.1 ng g −1 d −1 ) was significantly lower than that in the marsh (45.2 ng g −1 d −1 ). While Methanobacterium dominated in both habitats (41–59%), the overall composition of sediment methanogenic archaea communities differed significantly between the two habitats ( p < 0.05) and methanogenic archaea alpha diversity was lower in the aquaculture ponds ( p < 0.01). Network analysis revealed that interactions between sediment methanogenic archaea were much weaker in the ponds than in the marsh. Overall, these findings suggest that conversion of marsh land to aquaculture ponds significantly altered the sediment methanogenic archaea community structure and diversity and lowered the sediment's capacity to produce CH4 . Graphical abstract: Image 1 Highlights: Converting marsh to aquaculture ponds lowered sediment CH4 production potential. Sediment methanogenic archaea diversity and connectivity decreased after conversion. Methane production potential was higher in summer and autumn in both habitats. Key drivers were sediment carbon, SO4 2−, and methanogenic archaea diversity.